Management of Organizational Culture and Organizational Learning as Variables in Improving Performance - M. Irfani Hendri (Publikasi Indonesia, 2023)
The commodity of crude palm oil (CPO) from time to time has more profitable business prospects. Indonesia and Malaysia are the largest CPO producing countries in the world. The availability of large enough land is one of the factors that makes Indonesia a major producer of CPO for the world community. However, the productivity of oil palm plantations in Indonesia is still low compared to Malaysia. This then becomes the rationale that improving the performance of oil palm plantation companies is not only related to the availability of land, technology or capital. However, another important thing that needs to be done is how oil palm plantation companies manage organizational culture and organizational learning activities. This study aims to determine the effect of organizational culture and organizational learning on the performance of employees of PTPN XIII (Persero) which is a coconut plantation company. The sample in this study were employees of class III - IV PTPN XIII (Persero) who served in West Kalimantan. The data analysis model uses Partial Least Square (PLS). The results show that organizational culture has a significant effect on employee performance with a positive relationship direction, while organizational learning has no significant effect on employee performance with a positive relationship direction. This means that organizational learning has very little effect on employee performance.